(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The essence of the definition "self-realization" is analyzed in the article, the interrelation and interdependence of its activity-purpose, value-semantic, motivational-demanding and evaluative-reflective characteristics is revealed. Attention is focused on the structural and functional components of self-realization.